Play and fun in learning ethics education - Zakaria, Noor Syamilah; Saripan, M. Iqbal; Ismail, Alyani; Subarimaniam, Neerushah (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
Ethical competency is critical to the well-being of professionals. Ethical issues and decision-making process permeate the profession, and living ethically can be articulated as projecting the highest standard of belief system. In this research, the engineering ethics education instructor will use gamification in disseminating knowledge and conducting course activities. Gamification introduces a new idea which brings together the elements of play and fun in learning such a cut and dry course. Gamification in teaching engineering ethics education enables creative and intuitive skills, which may engage learners to experience course contents in more attractively and effectively. For this research, there will be a mobile application called Ethoshunt™ to be utilized in teaching engineering ethics education course. The objective of this conceptual research is to identify how ethics education is learned, understood, experienced and applied by the engineering students which utilizes gamification to their evolving professional identity and work in the program. This research will employ qualitative research design and use interpretive case study genre. The research will involve classroom observations and individual in-depth interview sessions. The interview information will be transcribed and documentations will be collected from course assignments. The researchers will comprehensively review the relevant literature to frame and refine the emergent findings. Coding categories will be developed using data analysis software on an ongoing basis, until the tentative sub-themes emerge and become the emergent master themes. This research may have impact on development and quality of teaching and learning new paradigm towards improving the quality and competitiveness of graduates. This research may also contribute a substantial change within engineering programs and generate a new strategy in teaching ethics education for future engineers.